2012
DOI: 10.1152/ajpcell.00209.2011
|View full text |Cite
|
Sign up to set email alerts
|

TRPM5 is critical for linoleic acid-induced CCK secretion from the enteroendocrine cell line, STC-1

Abstract: Fatty acidinduced stimulation of enteroendocrine cells leads to release of the hormones such as cholecystokinin (CCK) that contribute to satiety. Recently, the fatty acid activated G protein-coupled receptor GPR120 has been shown to mediate long-chain unsaturated free fatty acidinduced CCK release from the enteroendocrine cell line, STC-1, yet the downstream signaling pathway remains unclear. Here we show that linoleic acid (LA) elicits membrane depolarization and an intracellular calcium rise in STC-1 cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 29 publications
0
48
1
Order By: Relevance
“…The ability of STC-1 cells to produce and secrete CCK is thought not to require internalisation of the FA as an external receptor seems to induce CCK secretions (Choi et al, 2007, Tanaka et al, 2008, Shah et al, 2011. After 4 h exposure to the studied protein/FA complexes, no effect on CCK secretion was detected, whereas mRNA CCK levels differed between samples.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ability of STC-1 cells to produce and secrete CCK is thought not to require internalisation of the FA as an external receptor seems to induce CCK secretions (Choi et al, 2007, Tanaka et al, 2008, Shah et al, 2011. After 4 h exposure to the studied protein/FA complexes, no effect on CCK secretion was detected, whereas mRNA CCK levels differed between samples.…”
Section: Discussionmentioning
confidence: 90%
“…Relatively little is known concerning the mechanisms whereby nutrients influence CCK synthesis and secretion. Several studies have shown that peptides and FA can use an external receptor to induce CCK secretions (Choi et al, 2007, Tanaka et al, 2008, Shah et al, 2011. In vivo and in vitro studies indicate that proteins increase CCK secretion (Beucher et al, 1994, Cordier-Bussat et al, 1997, Nishi et al, 2001).…”
Section: Cholecystokinin (Cck) Is a Peptide Hormone Reported To Have mentioning
confidence: 99%
“…It is suggested that the sensory attributes of complex-tasting divalent salts are also mediated by TRPM5 and TRPV1 channels (42). TRPM5 is also essential for fat taste (23) and for linoleic acid-induced CCK secretion from the enteroendocrine cell line STC-1 (44). TRPM5 is a highly temperature-sensitive, heatactivated channel that may underlie known effects of temperature on perceived taste, including the enhanced sweetness perception at high temperatures, in humans (46).…”
mentioning
confidence: 99%
“…They have indicated that certain GPCRs were present upstream of this transduction mechanism. Additionally, Shah et al 37) have demonstrated that, although not present in taste cells but in STC-1, an enteroendocrine cell line, TRPM5 played a critical role in cholecystokinin (CCK) release by linoleic acid stimulation. The stimulation of GPR120 was necessary in the release of glucagon-like peptide-1 (GLP-1) 38) and CCK 39) with LCFA from the same cell line.…”
Section: Discussionmentioning
confidence: 99%